Substance Use Treatment Engagement among Men Who Have Sex with Men Who Use Stimulants in the Northeastern United States. (16th February 2022) - Viera, Adam; Sosnowy, Collette D.; van den Berg, Jacob J.; Mehta, Nikita A.; Edelman, E. Jennifer; Kershaw, Trace; Chan, Philip A.
Abstract: Background: Stimulant use is increasing in the United States (U.S.), especially among men who have sex with men (MSM). Objectives: We sought to ascertain barriers and facilitators to substance use treatment utilization among MSM who use stimulants in the northeastern U.S. Methods: We conducted semi-structured interviews with MSM who reported recent stimulant use. Interviews explored perceptions of and experiences with substance use treatment. We used thematic analysis to identify factors that facilitated or impeded substance use treatment engagement. Results: We interviewed 21 MSM in Providence, Rhode Island ( n = 15) and New Haven, Connecticut ( n = 6). Most participants identified as White (57.1%) and gay (52.4%). Over half (52.4%) screened positive for stimulant use disorder. We identified themes in how participants defined, entered, and engaged in substance use treatment. Participants described treatment to include a variety of modalities, including self-help and peer support groups; they defined treatment as an iterative process. Social networks played both a supportive and obstructive role in treatment entry depending on the relationships and approaches of network members. Meanwhile, social connection during treatment could be both therapeutic (reducing isolation) and counterproductive (precipitating cravings to use). Participants generally expressed a desire for harm reduction approaches to treatment over abstinence-only ones. Finally, participants did not find treatment responsive to their needs as MSM. Conclusion: This study highlights key barriers and facilitators to substance use treatment engagement and underscores the urgent need for culturally-responsive treatment programs that employ harm reduction approaches and are tailored to the unique circumstances of MSM who use stimulants. Supplemental data for this article is available online at http://dx.doi.org/10.1080/10826084.2022.2026965